The Role of Caseworkers in Unemployment Insurance: Evidence from Unplanned Absences - Amelie Schiprowski (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Caseworkers are the main human resources used to provide social services. This paper asks if, and how much, caseworkers matter for the outcomes of unemployed individuals. Using large-scale administrative data, I exploit exogenous variation in unplanned absences among Swiss UI caseworkers. I find that individuals who lose a meeting with their caseworker stay unemployed 5% longer. Results show large heterogeneity in the personal impact of caseworkers: the effect of a foregone meeting is zero for caseworkers in the lower half of the productivity distribution, while it amounts to more than twice the average effect for caseworkers in the upper half.
Keywords: 330